Challenges and opportunities of wood harvesting in Karelia, Russia: focus on a small-sized enterprise - Fadeeva, Natalia (Jyväskylän ammattikorkeakoulu, 2017)
The project was assigned by LLC “SpecTransLes”. The aim of the project was to collect and present data on the condition of logging business in the Republic of Karelia, increase understanding about the problems existing in the industry and influencing its logistics, as well as study and propose opportunities of the future development. Various sources of information such as books, journals, working and conference papers, scientific articles available both on-line and in libraries, as well Russian forest legislation, regulations and logging enterprise’s documents were studied to deeply familiarize the author with the study field and formulated research problem. Observations during internship at a company, along with interviews in order to collect data, explore the problems at the root, understand professionals’ experiences on the topic were done. The research was done based on qualitative and quantitative methods. As an outcome, the possible ways of development for LLC “SpecTransLes” were proposed. With the help of better technologies and innovations, investments, new educational policy in forestry field, federal support and development projects for wood harvesting enterprises, the timber production would be up-to- date and efficient, thus, allowing harvesting enterprises to utilize competitive advantage of the Republic at full extent.